HPWP Climate, Collective Well‐Being, and Firm Performance in SMEs: An Exchange Perspective - Tuteleers, Chloé; De Winne, Sophie; Wessa, Patrick; Wille, Bart (Human resource management, 2025)
ABSTRACT Research on High‐Performance Work Practices (HPWP) typically examines employees' aggregated HPWP perceptions and their impact on organizational outcomes. We argue that variability in these perceptions also matters due to its impact on collective exchange relationships. We integrate the aggregated (mean) level HPWP perceptions and variability regarding HPWP perceptions to identify four HPWP climate types: a strong HPWP climate (high mean, low variability) and three weak HPWP climates—unshared high (high variability, high mean), shared low (low variability, low mean), and unshared low (high variability, low mean). Using data from 695 employees in 72 Belgian SMEs, we find that a strong HPWP climate is optimal as it relates to the highest collective social and lowest economic exchange levels, which are—in turn—associated with high collective affective organizational commitment (CAOC) and subjective firm performance. However, it is also linked to high collective exhaustion, showing that aligning organizational and workforce interests is not always possible. As regards the weak climates, they are suboptimal, with shared low climates being particularly detrimental. Even though these climates can be fruitful for firm performance, they are linked to lower levels of CAOC, which can be harmful for SMEs that rely heavily on the effort and engagement of their employees. These findings show that investing in HPWP is fruitful for SMEs, even though they have limited financial means, and that SMEs also need to handle the inherent tensions present in HRM.